Effects of poor eating habits on children's body weight - Mirela Lisičić-Konaković; Senka Mesihović-Dinarević; Elmedin Bajrić; Sanja Jurišić; Ines Musa-Trolić; Mladen Ćubela; Zdenko Šarac; Jasminka Prguda-Mujić; Amila Zukanović (Elsevier, 2024)
The primary objective of this research is to delve into the correlation between suboptimal dietary habits and the body weight of children residing in Mostar city, Bosnia and Herzegovina. By examining the dietary patterns prevalent among the youth in this specific urban setting, the study seeks to uncover how these habits may be linked to variations in body weight. Through a comprehensive investigation, the aim is to contribute valuable insights into the intricate relationship between eating behaviors and the physical well-being of children in Mostar, thereby informing potential interventions or strategies for promoting healthier lifestyles within this population. In conclusion this pattern of dietary habits not only influences physical health but also has implications for overall well-being and may pose challenges for the long-term health trajectory of school-age boys. It underscores the importance of promoting healthier dietary choices and lifestyle habits from an early age to mitigate the potential adverse effects on children's health.